RECLAMATION STATE OF HYDROMORPHIC SOILS OF CENTRAL FERGANA AND THEIR FERTILITY - U. B. Mirzayev; M. A. Yusupova; A. R.Tojimatov (Web of Journals Publishing, 2025)
The article discusses the reclamation status of meadow-sedge soils formed in the Central Fergana Steppe, changes in them, and the formation of soil fertility in connection with them.
Keywords: Collector, dry residue, re-salination, desalination, brine, seepage waters, easily soluble salts in water, fertility.